2011
DOI: 10.1002/cncr.26068
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of tasisulam sodium (LY573636 sodium) as second‐line treatment for patients with unresectable or metastatic melanoma

Abstract: BACKGROUND: Tasisulam sodium (hereafter, tasisulam) is a novel anticancer agent that induces apoptosis through the intrinsic pathway and has antiangiogenic activity in preclinical models. Tasisulam demonstrated activity across a broad range of tumors, including melanoma. The primary objective of this phase 2 study was to determine the objective response rate (ORR) in patients who had received 1 previous systemic chemotherapy for unresectable/metastatic melanoma; secondary objectives were to evaluate the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Tasisulam is a promising drug which is used as an antiproliferative agent in patients with metastatic melanoma and other solid tumors [10,13,14,15,16]. A randomized, open-label clinical trial of tasisulam sodium versus paclitaxel as second-line treatment in patients with metastatic melanoma has recently been stopped early because of safety issues in the tasisulam arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tasisulam is a promising drug which is used as an antiproliferative agent in patients with metastatic melanoma and other solid tumors [10,13,14,15,16]. A randomized, open-label clinical trial of tasisulam sodium versus paclitaxel as second-line treatment in patients with metastatic melanoma has recently been stopped early because of safety issues in the tasisulam arm.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro, antitumor screening analysis conducted by the National Cancer Institute (NCI COMPARE analysis) demonstrated a broad range of activity for tasisulam in 60 tumor cell lines including leukemia, melanoma, non-small-cell lung cancer, colon, ovarian, renal, and breast cancers [12]. Subsequently, tasisulam was evaluated as a single agent in several tumor types [10,13,14,15,16]. In this study we focused on the antiproliferative effect of tasisulam and a newly synthesized sulfonimidamide-based analog, which both were studied in melanoma cell lines in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were lysed using a 2-step protocol adapted from ref. 48. Cells were directly lysed with lysis buffer (20 mM Tris-HCl, 1% Triton X-100, 10 mM MgCl 2 , 10 mM KCl, 2 mM EDTA, 1 mM NaF, 1 mM sodium orthovanadate, 2.5 mM β-glycerophosphate, 10% glycerol, pH 7.5), scraped off the culture dish, sonicated, supplemented to 400 mM NaCl, sonicated and diluted to 200 mM NaCl.…”
Section: Tumour Tissue Microarrays National Cancer Institute Cancer mentioning
confidence: 99%
“…Furthermore, TGFbneutralizing antibody GC-1008 showed promises in phase I trial for metastatic melanoma and renal cell carcinoma (45). Smallmolecule inhibitor, LY-573636, used in phase II clinical studies in patients with metastatic NSCLC, soft tissue sarcoma, and melanoma, has also shown modest activity as a second/third-line therapy (46)(47)(48). These studies showed that inhibiting TGFb signaling pathway is safe, well tolerated in patients and could provide promising new therapeutics against tumor invasion.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%